Experiences of Higher Education students during the Covid19 confinement: advantages, disadvantages and differences between face-to-face and Remote Learning - Leal, Fátima (2021)
Corona Virus Disease 2019 led to a state of public health emergency, in so many countries. Preventive measures forced the regime of face-to-face classes, in higher education, to be interrupted and replaced by a system of non-face-to-face classes – Emergency Remote Teaching (ERT). This change has led to the need for adaptation by both teachers and students. Several studies were developed to understand these different perspectives (e.g. [1], [2], [3]). Also, in Portugal, emergency state was declared and universities changed their classes from face-to face to non-face-to-face regime. Researchers like Leal and Chaleta (2020) tried to understand difficulties that students felt when dealing with this new approach class system and found difficulties at cognitive, motivational, interpersonal relationships and personal and academic organization levels [4]. Using a qualitative methodology, this study sought to understand the experiences and perceptions of eight higher education students (age varying from 19 to 23 years old) who suddenly found themselves immersed in this context of remote learning. Interviews were developed and applicated. Content analysis was used, and significant units were categorised, according to Bardin (2008) [5]. Explored topics were students' perception of their experiences, the differences between the two systems, advantages and disadvantages they recognize in the non-face-to-face classroom system. The main results of this study reveal a positive perception, a negative perception, and a change of perspective in the opinion about the classes in a non-face-to-face format. Advantages were found in academic, economic-financial and personal-developmental terms. The pointed-out disadvantages were at a personal, academic and social level. We conclude that these findings can be very useful in the teaching-learning process. For students in a general way, once they can identify with these verbalizations, they can feel that they are not alone in their academic issues and this can lead to motivating positive changes. For teachers, these results can serve as guidance on some aspects that may have gone better or worse, and accordingly, they may change and adapt their practices to the emergency remote teaching system. On the other hand, higher education institutions can also use these informations about learners experiences to the develop specialized helping programmes to their students(e.g., [6]).